(untitled) (Journal of Geography and Environmental Management, 2016)
In the modern world, human resources development, and effective territorial organization of economy are closely connected with the cities. The cities where human development success are concentrated are influencing not only the settlements near those cities, but also social and economic condition of whole region and country. It is very important for researchers to study in detail, on the one hand, the role of cities in territorial development, on the other hand, the life safety of the natural and technological systems and patterns of economic development. Thus, given article deals with the theoretical issues of ensuring innovative development of urban areas. We made analysis of theoretical conclusions of scientists such as J. Boudeville, N.D. Kondratiev, M. Porter, etc., who studied issues of spatial development of urban areas. The possibility of applying the theoretical concepts related to city geography for cities in Kazakhstan was considered.